A COMPARATIVE BIOGEOGRAPHICAL STUDY OF MYXOMYCETES IN FOUR DIFFERENT HABITATS OF EASTERN MEDITERRANEAN PART OF TURKEY - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2016)
In this study, Myxomycetes were collected from four different habitats of Hatay province of Turkey during 2010-2015, including Altinozu plateau, Belen Atik highland, Kirikhan Amik plain and Yayladagi Selcen Mountain. From identificated 1047 samples, 102 species were classified in 6 orders, 12 families and 28 genera. 27 species were obtained from natural environment while 114 species cultered by moist chamber technique. In addition, 61 species was obtained from both natural environment and moist chamber technique. Physarales is the highest proportion order (29.4%), followed by Trichiales (25.4%) and Stemonitales (24.5%). The total myxomycetes ratio of these three orders was determined as 79.4%. When samples from four different habitats compared in terms of substrate types, at three habitats, dominant species is lignicol Myxomycetes (65-85%), while at one habitat, corticol Myxomycetes (65%) is the dominant type. Arcyria cinerea, Comatricha ellae, Comatricha nigra, Echinostelium minutum and Stemonitopsis amoena is the most generous species at four areas. Moreover, morphological, chorological and ecological characteristics of Myxomycetes were discussed.
Keywords: Biogeography; Myxomycetes; Taxonomy; Hatay; PATTERNS; ECOLOGY; RECORDS; FORESTS; BIODIVERSITY; TREES